Oral complex rehabilitation in periodontally compromised patient. Clinical case report and follow-up for 6 years - Gonzales-Mattos, Jeanette (2020)
The oral rehabilitation of periodontally compromised patients present a clinical challenges because takes many sensible steps, especially the patient's commitment to perform a maintenance plan. Therefore, in order to achieve the expected results, a multidisciplinary treatment involving specialties that work under a coordinated treatment plan is essential. The introduction of dental implants has provided benefits to leading to improving the quality of life and the satisfaction of the patient. In the present article a clinical case of a periodontal compromised patient is related, treatment and follow-up for six years to the success of such treatment an implant supported rehabilitation type hybrid prosthesis in the maxilla and crowns cemented on implants in the lower jaw is reported following a protocol that provides us with adequate treatment predictability and high patient satisfaction.